Analisis Finansial Usahatani Kopi Sertifikasi dan Non Sertifikasi di Kecamatan Air Naningan Kabupaten Tanggamus - Anwar, M. Safrizal; Prasmatiwi, Fembriarti Erry; Endaryanto, Teguh (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The aim of this research is to analyze (1) the financial feasibility and (2) the sensitivity of coffee farming. The research was conducted in the villages of Karang Sari and Sidomulyo, Air Naningan Subdistrict, Tanggamus Regency, using a survey method. The respondents consisted of 41 certified farmers and 41 non-certified farmers. Data collection was carried out from May to June 2022. The analysis used includes financial metrics (NPV, Gross B/C, Net B/C, IRR, dan PP). Sensitivity analysis was conducted using various scenarios until one of the financial criteria was deemed unfeasible. The results of the study indicate that (1) both certified and non-certified coffee farming are feasible and profitable for development, and (2) sensitivity of certified farmers indicates a maximum limit of cost increase by 32.00 percent (monoculture coffee) and by 57.00 percent (polyculture coffee), as well as a decrease in coffee production by 25.00 percent (monoculture) and by 43.00 percent (polyculture). Meanwhile, non-certified have a maximum limit of cost increase by 4.00 percent (monoculture coffee) and by 24.00 percent (polyculture coffee), with a decrease in coffee production by 4.00 percent (monoculture) and by 23.00 percent (polyculture). When below these values, both certified and non-certified farmers are feasible and profitable for development.